Hollow marketing and nongredients: A new marketing approach by food industries in advertising - Nima S. Salami (Westcliff University, 2018)
Many firms that are selling food products, are hoping to get more of customers' attention, and increase their sales by new marketing strategies. Informing customers about ingredients and health claims look normal but advertising the things that can't inherently and naturally exist in their food, or "nongredients," are new practices that have been termed in this paper as "hollow marketing." This paper explains this new phenomenon, and its possible economic and social outcomes.